The impact of gestational weight gain on fetal and neonatal outcomes: the Araraquara Cohort Study - Audêncio Victor; Laísla de França da Silva Teles; Isabel Oliveira Aires; Leticia Falcão de Carvalho; Liania A. Luzia; Rinaldo Artes; Patrícia H. Rondó (BMC, 2024)
Abstract Background Gestational weight gain (GWG) is an important indicator for monitoring maternal and fetal health. Objective: To evaluate the effect of GWG outside the recommendations of the Institute of Medicine (IOM) on fetal and neonatal outcomes. Study design A prospective cohort study with 1642 pregnant women selected from 2017 to 2023, with gestational age ≤ 18 weeks and followed until delivery in the city of Araraquara, Southeast Brazil. The relationship between IOM-recommended GWG and fetal outcomes (abdominal subcutaneous tissue thickness, arm and thigh subcutaneous tissue area and intrauterine growth restriction) and neonatal outcomes (percentage of fat mass, fat-free mass, birth weight and length, ponderal index, weight adequateness for gestational age by the Intergrowth curve, prematurity, and Apgar score) were investigated. Generalized Estimating Equations were used. Results GWG below the IOM recommendations was associated with increased risks of intrauterine growth restriction (IUGR) (aOR 1.61; 95% CI: 1.14-2.27), low birth weight (aOR 2.44; 95% CI: 1.85-3.21), and prematurity (aOR 2.35; 95% CI: 1.81-3.05), and lower chance of being Large for Gestational Age (LGA) (aOR 0.38; 95% CI: 0.28-0.54), with smaller arm subcutaneous tissue area (AST) (-7.99 g; 95% CI: -8.97 to -7.02), birth length (-0.76 cm; 95% CI: -1.03 to -0.49), and neonatal fat mass percentage (-0.85%; 95% CI: -1.12 to -0.58). Conversely, exceeding GWG guidelines increased the likelihood of LGA (aOR 1.53; 95% CI: 1.20-1.96), with lower 5th-minute Apgar score (aOR 0.42; 95% CI: 0.20-0.87), and increased birth weight (90.14 g; 95% CI: 53.30 to 126.99). Conclusion Adherence to GWG recommendations is crucial, with deviations negatively impacting fetal health. Effective weight control strategies are imperative.